The effects of oregano essential oil on production performance and intestinal barrier function in growing Hyla rabbits - Chenyang Li (Taylor & Francis Group, 2021)
The purpose of this study was to investigate the effects of oregano essential oil on the production performance and intestinal barrier in rabbits. One hundred and ninety-two weaned Hyla rabbits (35 days old) with similar body weight (1268.5 ± 25 g) were randomly divided into four groups (24 replicates per group, two rabbits per replicate): fed a basal diet (Control group), fed a basal diet containing 0.02% oregano essential oil (LO group, the purity of oregano essential oil was 5%), fed a basal diet containing 0.04% oregano essential oil (MO group), or fed a basal diet containing 0.08% oregano essential oil (HO group). The trial included 7 days of adaptation and 23 days of testing. Although dietary addition of oregano essential oil did not affect significantly the average daily body weight and final body weight (p > .05), dietary addition of 0.08% oregano essential oil decreased significantly feed intake and diarrhoea rate of the rabbits (p < .05). When the addition of oregano essential oil in the feed reached 0.08%, the Villus high/Crypt depth value in the ileum of meat rabbits increased significantly (p < .05). Dietary addition of 0.08% oregano essential oil increased significantly the gene expression of junctional adhesion molecule 2 (JAM2) and JAM3 in jejunum (p < .05). The content of interleukin-2 (IL-2) and immunoglobulin A (SIgA) in jejunum and IL-10 and secretory immunoglobulin G (SIgG) in ileum were significantly increased after the addition of 0.08% oregano essential oil compared with the control (p < .05). In conclusion, a dietary supplement of oregano essential oil modulates immune responses and enhances the intestinal barrier. Besides, our experiment offers positive evidence in improving rabbit health of oregano essential oil instead of antibiotics.HIGHLIGHTS Oregano essential oil can improve the production performance of rabbits. Oregano essential oil improved intestinal barrier function in rabbits. Oregano essential oil can be used as a new additive in rabbit feed.